INVESTIGATING THE INFLUENCE OF FINANCIAL REPORTING TRANSPARENCY ON INVESTOR DECISION-MAKING - Redjeki, Finny; Aripin, Zaenal; Ruchiyat, Endang (KRIEZ ACADEMY : Journal of development and community service, 2024)
BackgroundTransparency in financial reporting is integral to the functioning of modern financial markets, as it enables investors to make informed decisions. In an increasingly interconnected global economy, where markets are influenced by diverse factors such as regulatory standards, technological advancements, and corporate governance practices, the need for clear, reliable, and accessible financial data has become even more critical. Previous financial crises, such as the 2008 global financial meltdown, highlighted the damaging effects of inadequate transparency, leading to significant losses for investors. This study investigates the influence of financial reporting transparency on investor decision-making, exploring the interplay between regulatory compliance, technological innovation, and investor behavior. AimsThe primary aim of this study is to examine the impact of financial reporting transparency on investor decision-making, focusing on how clear and accurate financial disclosures shape investor confidence and market participation. The research seeks to explore the relationship between transparency levels, technological advancements, regulatory compliance, and investor perception across different sectors. By doing so, the study aims to provide actionable insights for firms, regulators, and investors to enhance decision-making processes in financial markets. Research MethodThis research adopts a mixed-method approach, combining quantitative data analysis and qualitative insights. Quantitative data were collected from publicly available financial reports of 50 publicly listed companies across various sectors over a five-year period (2018-2022). Key financial indicators such as earnings per share (EPS), return on equity (ROE), and debt-to-equity ratios were analyzed to assess the clarity and consistency of financial disclosures. Qualitative data were gathered through semi-structured interviews with 30 individual and institutional investors, focusing on their perceptions of transparency, trust in financial reports, and challenges in interpreting financial data. The data were analyzed using statistical software for quantitative insights and thematic analysis for qualitative responses. Results and ConclusionThe study reveals a strong positive correlation between financial reporting transparency and investor confidence. Firms adhering to international reporting standards (such as IFRS) tend to attract higher levels of investment and foster greater trust among investors. Additionally, the adoption of advanced technologies like artificial intelligence (AI) and blockchain has been shown to enhance the accuracy and timeliness of financial disclosures, further improving transparency. Regulatory compliance also plays a significant role, with fully compliant firms experiencing higher investment flows and lower market penalties. However, challenges such as earnings management practices and perception gaps between individual and institutional investors highlight areas for improvement in financial reporting. The study concludes that enhancing transparency through clear disclosures, technological innovation, and regulatory adherence is crucial for fostering investor trust and improving decision-making. ContributionThis research contributes to the growing body of knowledge on financial transparency by providing empirical evidence of its impact on investor decision-making. It highlights the importance of transparent reporting, regulatory compliance, and technological advancements in shaping investor behavior and market dynamics. The findings offer practical recommendations for firms, regulators, and investors to enhance financial transparency and mitigate the risks associated with opacity in financial disclosures. Moreover, the study contributes to the understanding of the evolving role of technology in improving financial reporting practices, which has significant implications for the future of financial markets.